Aberrant brain functional network strength related to cognitive impairment in age-related hearing loss - Zhu, Shaoyun; Song, Jiajie; Xia, Wenqing; Xue, Yuan (Frontiers in Neurology, 2022)
Purpose Age-related hearing loss (ARHL) is a major public issue that affects elderly adults. However, the neural substrates for the cognitive deficits in patients with ARHL need to be elucidated. This study aimed to explore the brain regions that show aberrant brain functional network strength related to cognitive impairment in patients with ARHL. Methods A total of 27 patients with ARHL and 23 well-matched healthy controls were recruited for the present study. Each subject underwent pure-tone audiometry (PTA), MRI scanning, and cognition evaluation. We analyzed the functional network strength by using degree centrality (DC) characteristics and tried to recognize key nodes that contribute significantly. Subsequent functional connectivity (FC) was analyzed using significant DC nodes as seeds. Results Compared with controls, patients with ARHL showed a deceased DC in the bilateral supramarginal gyrus (SMG). In addition, patients with ARHL showed enhanced DC in the left fusiform gyrus (FG) and right parahippocampal gyrus (PHG). Then, the bilateral SMGs were used as seeds for FC analysis. With the seed set at the left SMG, patients with ARHL showed decreased connectivity with the right superior temporal gyrus (STG). Moreover, the right SMG showed reduced connectivity with the right middle temporal gyrus (MTG) and increased connection with the left middle frontal gyrus (MFG) in patients with ARHL. The reduced DC in the left and right SMGs showed significant negative correlations with poorer TMT-B scores (r = −0.596, p = 0.002; r = −0.503, p = 0.012, respectively). Conclusion These findings enriched our understanding of the neural mechanisms underlying cognitive impairment associated with ARHL and may serve as a potential brain network biomarker for investigating and predicting cognitive difficulties.